Revitalizing Urban Governance: Integrating Smart Growth and Decolonial Perspectives for Municipal Empowerment in Shaping Growth Across Egyptian Desert Landscapes - Anas Alhowaily (Alanya Üniversitesi, 2023)
This article explores the connection between Smart Growth and the decolonization of urban growth management in Egypt, examining the impact of former colonial influence on present urban policy and practices. Drawing insights from the urbanization of Egyptian desert areas before and after the New Urban Communities Program (NUCP), it scrutinizes how historical influences adversely affect contemporary approaches, inducing socio-economic impacts. The primary objective is to identify the root causes of misguided urban growth management practices, arguing that mono-institutional and sectoral development is rooted in Egypt's quasi-colonial history preceding the NUCP. The research employs a comprehensive methodological approach, using descriptive qualitative methods to investigate the growth of emerging cities based on Smart Growth principles and quantitative analysis to assess population decongestion resulting from the NUCP. It evaluates the implementation of Smart Growth principles during the NUCP and pre-NUCP, offering insights into adverse management practices. Despite the NUCP's goal to alleviate congestion, only 1.6 percent of the population was decongested by 2017. The research highlights the need for a new municipally guided growth model, emphasizing indigenous and locally validated approaches. This model aims to rectify inefficiencies in current urban management practices, fostering a responsive and sustainable approach aligned with local community needs.